Cultural Isolation, Identification, and Antibiogram of Escherichia coli from Commercial Layers Affected with Egg Peritonitis - Sheth, Aaftabhussain L.; Ghodasara, Dinesh J.; Mathakiya, Rafiyuddin A.; Solanki, Devasi M.; Dave, Chandrakant J. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was conducted on eight commercial layer flocks affected with egg peritonitis (swab samples from oviduct and exudate  from the peritoneal cavity) for cultural isolation, identification, biochemical characterization, and antibiogram of Escherichia coli (E. coli).  All the twenty-four samples from 8 commercial layer flocks revealed colonies with typical morphology and biochemical characteristics  of E. coli. Antibiogram study against seven different antibiotics was conducted by disc diffusion method. The results revealed the highest  (100%) sensitivity to antibiotic ceftriaxone, levofloxacin, and tetracycline, followed by amikacin (75.00%) and cefotaxime (62.50%), while  the organisms were highly resistant to norfloxacin (75.00%) followed by pefloxacin (62.50%).
Keywords: Antibiogram; Commercial layer; Cultural characteristics; Egg peritonitis